Feet to the fire : how to exemplify and create the accountability that creates great companies - Moore, Lorraine A. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
Today's global, transparent, and often-turbulent economy requires a new world order in leadership. The business environment has forever changed, and leaders have been caught flat-footed. Our heroes and heroines are hard to find. Many experienced leaders and certainly newer leaders are ill prepared for the imposing regulatory environment and community activism that permeates oil and gas/energy, health care, financial services, pharmaceuticals, and more. Talented, passionate, and committed people will change the world--for their customers, their colleagues, their shareholders, and their employees. However, to unleash people's potential, to generate recurring revenue growth, foster innovation, and maximize productivity, we need to hold each other's feet to the fire. We need to create a culture of accountability. What are the benefits of an accountable organization? They are numerous. Increased employee engagement, higher ROI on projects, retention of your best performers, improved customer loyalty; greater innovation and increased profitability all result from higher levels of accountability.
1. Creating a culture of accountability -- 2. Establishing a career without sacrificing a life -- 3. Constructing your leadership brand -- 4. Excelling at career turning points -- 5. Multifaceted leadership -- 6. Harnessing performance -- 7. Talent for the twenty-first century -- 8. Elevating others to soar: leading organizational change -- 9. Elevating results through innovation -- Index.
Includes index.
Title from PDF title page (viewed on December 17, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Organizational change; Executive coaching; Responsibility; accountability; career; career advice; CEO; consulting; Enbridge; executive performance; executive presence; implementation; innovation; leadership; leadership courage; leading in difficult times; leading others; mergers and acquisitions; performance; performance improvement; performance under pressure; self-awareness; strategic; strategy; succession; talent; talent management; TD; Electronic books